The ‘Halton model’ proposes how to evaluate a school (Journal of Parents and Teachers, 2026)
The London Institute of Education invited a number of experts to present what could be called guidelines for defining school outcomes. The ‘Halton model’ from the University of Ontario is divided into three core areas, from which other variables are derived that must be taken into account when evaluating educational effectiveness. Another idea developed in this section is about consumption and hunger figures that can be used in arithmetic classes. Finally, learn about two films about the life of Columbus, currently showing in many Spanish cinemas.
Keywords: evaluate the school, Halton model, consumption, hunger, arithmetic, Christopher Columbus